Habitat and population dynamics of wolves and blackbuck in Velavadar National Park, Gujarat - Jhala, Yadvendradev V. (Virginia Tech, 1991)
The management problem of allocating limited resources for conflicting habitat needs of 2 endangered species, (the wolf ( Canis lupus pallipes ) and the blackbuck ( Antelope cervicapra )) at Velavadar National Park, Gujarat, India, was addressed with the aid of mathematical optimization models. Critical biological data essential for model formulation and management decisions were collected by field research from February 1988 to December 1990. The semi-arid grassland habitat was dominated by perennial grasses like Dichanthium annulatum and Sporobolus virginicus . The grassland system seems quite resilient to droughts and grazing. Above-ground production is primarily dependent on precipitation. Two-year rainfall sequence explained 960/0 of the variability in the peak above-ground plant biomass. Food habits of blackbuck were determined by lead animal studies and observations on wild blackbuck. Blackbuck relied primarily on grasslands to obtain food. The pods of the exotic shrub, Prosopis juliflora , comprised 10% of the diet and were considered to be important during the summers and drought years. Dry matter intake, as estimated from captive blackbuck feeding on natural forage, was cyclical, dropping in the summers and increasing during the monsoons and winters. Apparent digestibility and forage quality were extremely low in summers. Average annual dry matter intake was estimated at 86 gms/ kg .075 of blackbuck per day. Relationships were developed for predicting forage quality from fecal ether extract and fecal nitrogen. The blackbuck population seemed to be in a dynamic equilibrium at about 1850 animals. Periodic droughts and floods cause major population declines. The population takes 4-5 years to recover from such catastrophic mortality. Life-table analysis done by aging jaws of dead blackbuck revealed a bimodal mortality pattern for males. Males between the ages of 7 to 9 years were at high risk of wolf predation during the rutting season. A population simulation model using a modified Leslie matrix approach ...